Magnetoliposomes as nanocarriers for fluorescent potential antitumor drugs - Castanheira, Elisabete M. S. (2018)
Both aqueous magnetoliposomes (AMLs, containing magnetic nanoparticles entrapped in liposomes) and solid magnetoliposomes (SMLs, where clusters of nanoparticles are covered by a lipid bilayer) containing several different nanoparticles (magnetite, nickel ferrite, manganese ferrite or magnesium ferrite) have been developed, exhibiting a superparamagnetic behavior and diameters below 150 nm.